Systemic cellular viroimmunotherapy for canine high-grade gliomas. Issue 12 (20th December 2022) - Cloquell, Ana; Mateo, Isidro; Gambera, Stefano; Pumarola, Martí; Alemany, Ramon; García-Castro, Javier; Perisé-Barrios, Ana Judith
Abstract : Background: Oncolytic viruses constitute a growing field of interest, both in human and veterinary oncology, given that they are particularly helpful for treating non-surgical tumors and disseminated cancer, such as high-grade gliomas. Companion dogs present malignant gliomas with biological, genetic, phenotypic, immunological, and clinical similarities to human gliomas. These features favor comparative approaches, leading to the treatment of canine oncological patients to achieve translational applications to the human clinic. The systemic administration of oncolytic viruses presents a challenge due to their limitations in effectively targeting tumors and metastases. Therefore, the aim of this study is to evaluate the safety and antitumor activity of a virotherapy used in spontaneous canine tumors. Methods: Ten dogs with high-grade rostrotentorial gliomas underwent weekly systemic endovenous cellular virotherapy with dCelyvir (canine mesenchymal stem cells infected with the canine oncolytic adenovirus ICOCAV17) for 8 weeks. Efficacy was determined in seven dogs according to the Response Assessment in Veterinary Neuro-Oncology criteria considering clinical status and MRI measurements. Medical history, physical and neurological examinations, and vaccination status were evaluated prior to and during follow-up. Safety was evaluated by physical examinations and hematological and biochemical changes in peripheral blood. Immune populations were analyzed by flow cytometry in peripheral blood and by gene expression and immunohistochemistry in the tumor microenvironment. Results: The treatment was well tolerated and major adverse effects were not observed. Two dogs had partial responses (76% and 86% reduction in tumor size), and 3/7 showed stable disease. ICOCAV17 was detected in peripheral blood in nine dogs, and a correlation between the ICOCAV17 particles and anti-canine adenovirus (CAV) antibodies was observed. ICOCAV17 was detected in 3/9 tumor tissues after necropsies. Regarding tumor-infiltrating lymphocytes, the dogs with disease stabilization and partial response tended to have reduced memory B-cell infiltration and increased monocyte/macrophage lineage cells. Conclusions: These findings indicate that dCelyvir is safe and presents efficacy in canine rostrotentorial high-grade gliomas. These data are relevant to the ongoing phase Ib regulated human clinical trial that is administering this virotherapy to children, adolescents, and young adults with diffuse pontine glioma. Celyvir should be further explored as a treatment in veterinary and human neuro-oncology.